Хелатні комплекси Сu(ІІ) з флуоровмісними лігандами: синтез, будова, антиоксидантні та протизносні властивості - Yevdokymenko, Vitaliy O.; Pylyavsky, Volodymyr S.; Kamenіeva, Tetyana M.; Shishkina, Svitlana V.; Gerus, Igor I.; Khimach, Nataliia Yu. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
Improving the antioxidant and antiwear properties of alternative ethanol-based motor fuels is a pressing problem in petrochemistry. The most rational way to solve this problem is currently considered to be the addition of metal complex compounds in small concentrations to the composition of such fuels. Copper(II) chelates with fluorinated 1,3-diketones, hexafluoroacetylacetone, etc., due to their high volatility and stability, are used in many application areas. However, the use of copper(II) chelate with hexafluoroacetylacetone as an additive to high-tonnage petroleum products (motor fuels and oils) is hindered by the high price of fluorinated 1,3-diketones. The use of fluorinated 1,3-ketoaldehydes, trifluoroacetylacetaldehyde, etc. can solve this problem and increase the stability of such copper(II) chelates. A series of copper(II) chelates with fluorine-containing ligands of different structures was synthesized, their structure and influence on the chemical properties of alternative ethanol-containing motor fuels were investigated. The antioxidant activity of copper(II) chelates was determined by the volumetric method (gasometric setup) on a model reaction of initiated radical-chain oxidation of benzyl alcohol (thermal initiator – 2,2΄-azo-bis-isobutyronitrile, free radical generation rate Wi = 2.98 10–8 М·s–1, temperature – 50±0.2 °C, partial oxygen pressure – 0.02-0.1 MPa). The dependence of the antiwear properties of ethanol solutions on the concentration of copper(II) chelates was evaluated by the change in the bearing capacity (dynamic strength) of the solution according to the ASTM D2783 method on a four-ball tribometer at the critical load value. It was established that the synthesized fluorine-containing copper(II) chelates are inhibitors of the catalytic action of chain breakage in the oxidation of benzyl alcohol, which leads to a long-term inhibition of its oxidation process. The fact of a significant (by 40-65 %) increase in the antiwear properties of ethanol solutions when copper(II) chelates are introduced into their composition in low concentrations of 0.001-0.01 wt. % was revealed. The prospects of using ultra-low concentrations of synthesized metal complexes for improving the chemical properties of alcohol-containing motor fuels were shown.